2018
DOI: 10.1371/journal.pone.0198493
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of Pantoea agglomerans-derived lipopolysaccharide prevents metabolic dysfunction and Alzheimer’s disease-related memory loss in senescence-accelerated prone 8 (SAMP8) mice fed a high-fat diet

Abstract: The pathogenesis of Alzheimer’s disease (AD) remains unclear, but an imbalance between the production and clearance of amyloid-β (Aβ) peptides is known to play a critical role in AD progression. A promising preventative approach is to enhance the normal Aβ clearance activity of brain phagocytes such as microglia. In mice, the intraperitoneal injection of Toll-like receptor 4 agonist was shown to enhance Aβ clearance and exhibit a preventative effect on AD-related pathology. Our previous clinical study demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 49 publications
3
32
0
1
Order By: Relevance
“…These results suggested that L. paracasei KW3110 could activate the gut immune cells inducing IL-10 production. In a previous report, oral administration of Pantoea agglomerans -derived lipopolysaccharide reduced proinflammatory cytokine expression in the blood and reduced the brain Aβ burden and memory impairment [30]. These results suggested that the regulation of cytokine levels, induced by oral administration of food constituents, might have the potential to affect the inflammatory state of the peripheral tissues through systemic blood flow.…”
Section: Discussionmentioning
confidence: 67%
“…These results suggested that L. paracasei KW3110 could activate the gut immune cells inducing IL-10 production. In a previous report, oral administration of Pantoea agglomerans -derived lipopolysaccharide reduced proinflammatory cytokine expression in the blood and reduced the brain Aβ burden and memory impairment [30]. These results suggested that the regulation of cytokine levels, induced by oral administration of food constituents, might have the potential to affect the inflammatory state of the peripheral tissues through systemic blood flow.…”
Section: Discussionmentioning
confidence: 67%
“…Recently, in vitro studies have reported that Pantoea agglomerans LPS (LPSp) markedly increases the phagocytic activity directed at Aβ1-42 peptides in a mouse microglial cell line as well as in primary microglia isolated from the mouse brain (Kobayashi et al, 2016(Kobayashi et al, , 2017. In addition, the oral administration of LPSp markedly prevented a memory deficit in high-fat diet-fed SAMP8 mice (Kobayashi et al, 2018) Also, rice bran is a rich natural source of antioxidant polyphenols, flavonoids, phytic acid, vitamin E, and γ-oryzanol (Moure et al, 2001); these useful ingredients are lost in the rice milling process used to produce WR (Tuncel & Yılmaz, 2011 TA B L E 8 Difference of the score of each item of HDS-R in the low cognitive function group in a high concentration in rice bran. Rice bran extract as a rich source of γ-oryzanol improved impaired mitochondrial function in a cell culture AD model (Hagl et al, 2015) and affected the activation of microglia in vitro (Bhatia, Baron, Hagl, Eckert, & Fiebich, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Physiological effects of LPS are expressed via toll-like receptor 4 present on the cell surface of the host cell (11). The plant symbiotic Gram-negative bacteria Pantoea agglomerans has been shown to be a useful microorganism that coexists with plants supplying them with nitrogen and phosphorus (12,13). To date, various treatments have been tested in the clinical setting using LPS derived from P. agglomerans (LPSp) (14, 15).…”
mentioning
confidence: 99%
“…Inagawa et al reported that they isolated LPSp from bacteria coexisting with wheat and that oral administration of LPSp increased the ability of macrophages to eliminate foreign substances in vivo (16). The group have also reported that the transdermal/oral administration of LPSp can improve the pathology of various chronic diseases (14,15,(17)(18)(19)(20)(21). Among them, administration of LPSp to mice as a model of Alzheimer's disease (caused by amyloid β accumulated in the brain) led to suppression of amyloid β accumulation and reduction in cognitive decline compared to control mice (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation